A study of SARS-CoV-2 delta variant breakthrough infections and side effects of the Oxford-AstraZeneca vaccine - Nawfal R. Hussein; Bizav Naji Rasheed; Ibrahim A. Naqid; Arshed Mustafa Dirbaz; Zana Sidiq M. Saleem; Nashwan Ibrahim; Dildar H. Musa; Sulav Muslih Mohammed (Elsevier, 2022)
Objective: This study aimed to investigate the breakthrough infection rate and safety profile of the AstraZeneca vaccine. Methods: The breakthrough COVID-19 infection rate was defined as a positive polymerase chain reaction test 14 days after the vaccine dose. Safety was assessed as local reactions and systemic events that occurred within 14 days of receiving vaccine doses. Results: The average age of the 265 participants was 43.85 years and 169 (63.77%) were male. . After the second dose, 18 (6.71%) participants contracted the infection. The SARS-CoV-2 delta variant was responsible for all infections but no participants required hospitalisation. We found significant correlations between post-vaccination IgG levels and post-vaccination infection (P = 0.001; odds ratio [OR] = 0.959; 95% Confidence interval [CI]: 0.944-0.974), and between a history of previous infection and post-vaccination infection rates (P = 0.005; OR = 0.1; 95%CI:0.009-0.6). IgG levels were significantly higher in women than in men (P = 0.006) and in patients who developed side effects after vaccination than in those without side effects (P = 0.04). A significant association was found between a history of COVID-19 infection prior to vaccination and IgG levels (P = 0.001). Conclusions: The vaccine is effective in preventing severe disease, with few side effects.